2020
DOI: 10.1101/2020.10.22.20217489
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frailty and comorbidity in predicting community COVID-19 mortality in the UK Biobank: the effect of sampling

Abstract: Frailty has been linked to an increased risk of coronavirus disease 2019 (COVID-19)-associated mortality, but evidence has been inconclusive and limited to hospitalized older individuals. Using data from the UK Biobank, we assessed whether frailty and comorbidity predict COVID-19 mortality in the overall community population (n=437,555) and in a selected COVID-19 positive sample (n=2,059). Frailty was assessed using the Rockwood Frailty Index (FI) and the Hospital Frailty Risk Score (HFRS), whereas comorbidity… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
(87 reference statements)
0
14
0
Order By: Relevance
“…Likewise, our metaregression does not include measures of comorbidities such as diabetes or obesity [156]. However, a recent study of data from a large representative and longitudinal sample collected by U.K. Biobank found that measures of frailty and comorbidity had only moderate effects in predicting COVID-19 mortality risk (i.e., increased odds of about 10%); moreover, that link was negligible among positive COVID-19 cases after accounting for age and sex [157]. See Supplementary Appendix S for additional evidence.…”
Section: Locationmentioning
confidence: 99%
“…Likewise, our metaregression does not include measures of comorbidities such as diabetes or obesity [156]. However, a recent study of data from a large representative and longitudinal sample collected by U.K. Biobank found that measures of frailty and comorbidity had only moderate effects in predicting COVID-19 mortality risk (i.e., increased odds of about 10%); moreover, that link was negligible among positive COVID-19 cases after accounting for age and sex [157]. See Supplementary Appendix S for additional evidence.…”
Section: Locationmentioning
confidence: 99%
“…In addition, we included serum C-reactive protein concentration, Charlson Comorbidity Index (CCI), and self-reported usage of non-steroidal anti-inflammatory drugs. CCI was constructed based on 17 comorbidities with assigned weights associated with ICD codes from inpatient data [28]. The medication information was obtained from the baseline medication information in touch-screen questionnaires and verbal interview, including use of non-steroidal anti-inflammatory drugs, antibiotics, proton-pump inhibitors, hormonal replacement therapy, and oral contraceptive pills.…”
Section: Assessment Of Covariatesmentioning
confidence: 99%
“…However, there is little difference in the rate of mortality between high and intermediate HFRS. This may be related to changes in the nature of the population presenting as a consequence of the national lockdown [ 28 ], or the availability of testing, which changed over the course of the pandemic. Indeed, we observed both changing populations presenting to acute care over the course of the pandemic (in part related to the imposition and subsequent lifting of lockdowns) and changing outcomes (perhaps related to changing treatment effects, such as the introduction of Dexamethasone [ 29 ]).…”
Section: Discussionmentioning
confidence: 99%